Dalbergia calcarea, a new species of Dalbergia (Fabaceae: Dalbergieae) from Lao PDR - Lanorsavanh, Soulivanh; Mattapha, Sawai; Lamxay, Vichith; Souvannakhoummane, Keooudone; Chanthavongsa, Khamfa (Thai Forest Bulletin (Botany), 2024)
Dalbergia calcarea, a new species currently only known from the limestone mountains of Khammouan Province, central Laos, is described and illustrated. The key characters such as habit, colour and limb of standard, and number of ovules of the new species are discussed and compared with its closest relatives. A detailed description along with etymology, conservation status, illustrations and colour photographs are provided for a new species. This discovery increases the number of Laotian species in the genus Dalbergia to seventeen taxa.